RANCANG BANGUN KONTEN E-LEARNING KEGIATAN PEMASANGAN WIFI INDIHOME MENGGUNAKAN METODE ADDIE DAN SECI PADA PT. MAP SUBANG - Yunia, Laras Maudy; Kusnadi; Fahrudin, Rifqi (P3M Politeknik Negeri Banjarmasin, 2023)
Knowledge is often associated not only with documents or valuable assets, but also with routines, processes, practices, and norms within a company. There are two types of knowledge: Tacit Knowledge and Explicit Knowledge. Tacit knowledge is knowledge derived from individual experiences that exists within their minds and is difficult to share with others. Tacit knowledge can be lost due to outsourcing, employee downsizing, company mergers, or when individuals leave their jobs. On the other hand, explicit knowledge is knowledge that can be documented, interpreted, and shared with others. PT MAP, a partner of PT Telkom Indonesia's fiber network Indihome, provides services such as sales, wifi installation, troubleshooting, and Indihome maintenance. The limitations and lack of learning processes for new technicians or technicians seeking to enhance their knowledge in wifi networks are the background issues in this research. The ADDIE method is one of the commonly used methods in e-Learning design. It consists of five stages: analysis, design, development, implementation, and evaluation. In the design stage, the conversion from tacit knowledge to explicit knowledge is carried out using the SECI method, which involves socialization, externalization, combination, and internalization. The use of the SECI method in the knowledge conversion process is based on the consideration that the data used is tacit knowledge from employees and company owners. Therefore, PT MAP requires an e-learning content that will help facilitate and accelerate the learning process for new employees and those who seek to enhance their knowledge.